Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Fantasies of femininity: Reframing the boundaries of sex - Ussher, Jane M. (Rutgers University Press, 1997)
In Fantasies of Femininity, Jane Ussher focuses on unraveling the contradictory visions of feminine sexuality: the fact that representations of the definition of woman seethe with sexuality yet for centuries women have been condemned for exploring their own sexual desires. In her quest for the sources of feminine representation, Ussher interviewed dozens of women - as well as some men - and combed popular media - from Seventeen to Cosmopolitan and Dallas to Donahue - to identify what shapes women's symbolic images of sex and femininity. Ussher argues that women have effectively resisted and subverted these archetypal fantasies of femininity, and in the process of so doing, reframed the very boundaries of sex. In this way, she exposes as myth much of what we think we know about "woman" and about "sex."
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychologie; sciences humaines; sexualité; sexualité féminine; stéréotypes; systèmes d'oppressions; thématiques; études culturelles